RANCANG BANGUN SISTEM INFORMASI MANAJEMEN BADAN USAHA MILIK DESA (BUMDES) BERBASIS WEB - Harahap, Ricky Ramadhan; Irwan, Irwan; Fachri, Barany; Ryanda, Fajar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Village asset management requires control from internal parties including employees and village officials. The manual system implemented so far is considered less efficient, so the development of an asset management information system is needed. This research aims to record data, and display information or reports on village assets electronically based on computers. The method of developing a village asset management information system used is System Developping Live Cycle (SDLC), using the PHP programming language and MySQL as a database storage. The results can be obtained in the form of a village asset management system designed to facilitate general administrative problems and has features to present reporting, facilitate asset codification, and accurate asset management according to the Minister of Home Affairs Regulation. Keywords: Inventory; Asset Management; Information System; SDLC; Village  Abstrak: Pengelolaan aset desa memerlukan adanya pengendalian dari pihak internal yang meliputi karyawan dan pejabat desa. Sistem manual yang dilaksanakan selama ini dianggap kurang efisien, sehingga dibutuhkan pengembangan sistem informasi pengelolaan asset. Penelitian in bertujuan untuk merekam data, dan menampilkan informasi atau laporan aset desa secara elektronik berbasis komputer. Metode pengembangan sistem informasi pengelolan aset desa yang digunakan adalah System Developping Live Cycle (SDLC), dengan menggunakan Bahasa pemrograman PHP dan MySQL sebagai tempat penyimpanan database. Hasil yang dapat diperoleh berupa sistem pengelolaan aset desa yang dirancang untuk memudahkan permasalahan administrasi umum dan memiliki fitur untuk menyajikan pelaporan, memudahkan kodefikasi aset, dan pengelolaan aset yang akurat sesuai Peraturan Mentri dalam Negeri Kata kunci: Inventaris; Pengelolaan Aset;Sistem Informasi;SDLC; Desa.